Synthesis, Docking Study and Biological Evaluation of Naproxen-Based Heterocyclic Deriva tives - Awad, Ammar A.; Maged, Mohammed N.; Abed, Dhulfiqar A.; Wennas, Osamah N.; Kbah, Noor Z.; Disher, Ayad A. (Karagandy University of the name of academician E.A. Buketov, 2025)
A series of Naproxen-based heterocyclic derivatives (NA1-NA4) were designed, synthesized, and evaluated for their antibacterial and anticancer activities. These heterocyclic derivatives were developed by integrating Naproxen with various heterocycles, including indole, benzothiophene, benzothiazole, and pyrazole, in order to enhance efficacy while reducing gastrointestinal side effects. The synthesized compounds were character ized using FT-IR, 1H NMR, and 13C NMR spectroscopy. The antibacterial activity was evaluated against S. aureus (Gram-positive) and two Gram-negative bacteria (P. aeruginosa and K. pneumonia) by measuring the diameter of the zone of inhibition. Compounds NA2 and NA3 showed promising inhibitory activity against the tested bacteria compared to amoxicillin. The anticancer activity of NA1-NA4 compounds against the MDA-MB-231 human breast cancer cell line was assessed by determining the IC50 values (the concentra tion required to inhibit 50 % of cell viability). NA1 and NA3 exhibited notable antiproliferative effects with IC50 values of 11.81 and 11.08 μg/mL, respectively. Molecular docking studies of compounds NA1-NA4 were performed against COX-2 enzyme (PDB Code: 3NT1) using MOE software. The compounds showed strong binding affinities, indicating potential anti-inflammatory properties. Collectively, the antibacterial, an ticancer, and molecular docking data suggest that these Naproxen derivatives possess promising multifunc tional therapeutic potential.
Keywords: Naproxen derivatives; heterocyclic compounds; COX-2 inhibition; MTT assay; antibacterial; anti cancer; breast cancer; anti-inflammatory properties